ENGINEERING GEOLOGICAL BEHAVIOUR OF HETEROGENEOUS AND CHAOTIC ROCK MASSES - Tsiambaos, G. (Bulletin of the Geological Society of Greece, 2010)
The engineering characterization of heterogeneous and complex geological formations for estimating their rock mass strength and deformability characteristics constitutes a challenge to geo-scientists and engineers dealing with the design and construction of slopes and tunnels. Mélanges and similar heterogeneous mixtures of hard blocks in weaker matrix, known as “bimrocks”, present an overall strength significantly greater than the matrix strength, because the presence of rock blocks, above a threshold volumetric proportion, influences the mechanical characteristics and the behaviour of these rock masses. Moreover, recent studies have shown that the strength and mechanical behaviour of heterogeneous and composite rock masses such as flysch and molasses consisting of alternating layers of competent and incompetent rocks are governed by the presence and volumetric percentage of the interlayers of the weaker rocks.